Geometrically Constructed Bases for Homology of Non-Crossing Partition Lattices - Kenny, Aisling (The Electronic Journal of Combinatorics, 2009)
For any finite, real reflection group W, we construct a geometric basis for the homology of the corresponding non-crossing partition lattice. We relate this to the basis for the homology of the corresponding intersection lattice introduced by Björner and Wachs using a general construction of a generic affine hyperplane for the central hyperplane arrangement defined by W.